Christian monasteries in Mosul and its impact in human civilization (Journal of the College of Basic Education, 2023)
The city of Mosul represents centers of intellectual radiation in all scientific fields, throughout the historical ages, through building educational institutions. The self-desire of the Mosul community was a motive for many people to learn and develop the intellectual movement.Monastery schools are no less active than their counterparts in the rest of the cities in spreading human and scientific sciences. Their interests have extended to include: medicine, arithmetic, astronomical sciences, etc. But what is regrettable is that our sources did not disclose mention of their activities in these fields, except for some indications that pertain to their works and their scientific status